2002
DOI: 10.1212/wnl.58.9.1418
|View full text |Cite
|
Sign up to set email alerts
|

Gender and pramipexole effects on levodopa pharmacokinetics and pharmacodynamics

Abstract: The authors studied the pharmacokinetics of levodopa (LD) with and without pramipexole (PPX) in men and postmenopausal women with PD. Patients on stable dose of carbidopa/LD were randomized to receive escalating doses of placebo or PPX over 7 weeks. LD and PPX pharmacokinetics were performed after a single test dose 25/100 of carbidopa/LD, before initiation of PPX or placebo, at 1.5 mg/d and 4.5 mg/d of PPX or placebo. Compared to men, women had greater LD bioavailability. PPX did not alter LD bioavailability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 13 publications
(14 reference statements)
2
41
2
Order By: Relevance
“…Because the changes in RNA levels precede the changes at the protein level, as shown for PEPT1 (Qandeel et al, 2009), we may have missed RNA changes that potentially took place earlier. Differences in the circadian cycle of male and females as observed in our study are not yet well understood (Bailey and Silver, 2014), but importantly, gender differences have also been suggested to play a major role in PD patients (Kompoliti et al, 2002;Steffansen et al, 2004;Miller and Cronin-Golomb, 2010;Pavon et al, 2010;Doi et al, 2012).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Because the changes in RNA levels precede the changes at the protein level, as shown for PEPT1 (Qandeel et al, 2009), we may have missed RNA changes that potentially took place earlier. Differences in the circadian cycle of male and females as observed in our study are not yet well understood (Bailey and Silver, 2014), but importantly, gender differences have also been suggested to play a major role in PD patients (Kompoliti et al, 2002;Steffansen et al, 2004;Miller and Cronin-Golomb, 2010;Pavon et al, 2010;Doi et al, 2012).…”
Section: Discussionmentioning
confidence: 52%
“…Absorption of levodopa in humans follows a circadian rhythm with faster absorption during day and delayed absorption during night (Nyholm et al, 2010). Furthermore, gender differences in levodopa bioavailability and in clinical presentation were observed (Kompoliti et al, 2002;Martinelli et al, 2003). We analyzed the expression of transporters involved in levodopa transport in the small intestine of male and female rodents during the active (related to daytime in humans) and nonactive phase (related to night-time in humans).…”
Section: Levodopa Transport In Intestinementioning
confidence: 99%
“…Other studies have also found a sex difference in bioavailability of the dopaminergic agonist, pramipexole, which is often used in conjunction with levodopa to potentiate the dopaminergic effect. In these studies, females were demonstrated to have a 24-27% lower oral clearance for pramipexole as compared to males [128]. This further suggests there is a sex difference in the clearance of dopaminergic agents that may play a role in sex-specific dosing of PD medications.…”
Section: Parkinson's Diseasementioning
confidence: 85%
“…Orally administrated levodopa in human is mainly decarboxylated in the GI tract (45) and in brain capillary endothelium (46) but also in liver and kidney. It has been shown that the bioavailability of levodopa is higher in women compared to men (47,48) and oestrogen is not the responsible factor (47). It is more likely the result of differences in COMT activity between gender (48).…”
Section: Levodopa In the Peripherymentioning
confidence: 99%